2013
DOI: 10.1159/000354714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Ultrapure Dialysate for Hemodialysis on the Level of Circulating Bacterial Fragment in Renal Failure Patients

Abstract: Background: Cardiovascular disease is the major cause of mortality and morbidity in dialysis patients. Recently, circulating endotoxin is found to associate with the systemic inflammatory state and cardiovascular disease of dialysis patients. Previous studies showed that the use of ultrapure dialysate for hemodialysis could reduce the exposure to exogenous endotoxin. We studied the effect of using ultrapure dialysate for hemodialysis on circulating endotoxin and bacterial DNA fragment levels and vascular stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 53 publications
(38 reference statements)
2
22
0
Order By: Relevance
“…76 In patients on hemodialysis, plasma endotoxin level fell by one third within 4 weeks of conversion to ultrapure dialysate. 77 In this study, the timeaveraged plasma endotoxin level correlated with serum CRP level, carotid-femoral PWV, and malnutrition inflammation score. 77 In essence, this study strongly supports the notion that circulating endotoxin has direct effects on systemic inflammatory state, and ultrapure dialysate is effective in reducing circulating endotoxin in patients on hemodialysis.…”
Section: Interventional Studiesmentioning
confidence: 59%
“…76 In patients on hemodialysis, plasma endotoxin level fell by one third within 4 weeks of conversion to ultrapure dialysate. 77 In this study, the timeaveraged plasma endotoxin level correlated with serum CRP level, carotid-femoral PWV, and malnutrition inflammation score. 77 In essence, this study strongly supports the notion that circulating endotoxin has direct effects on systemic inflammatory state, and ultrapure dialysate is effective in reducing circulating endotoxin in patients on hemodialysis.…”
Section: Interventional Studiesmentioning
confidence: 59%
“…However, we are not aware of any treatment that could increase the clearance of circulating DNA fragments. We have previously showed that using ultrapure dialysate for hemodialysis effectively reduces circulating endotoxin but not bacterial DNA level in hemodialysis patients [43]. Further clinical trials in this area are much needed.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of even slight amounts of bacterial endotoxins in the dialysate undermines the biocompatibility of HD therapy and may subsequently upregulate the formation of oxidative molecules . Several investigators suggested that HD with ultrapure dialysate may decrease plasma concentrations of inflammatory and OS markers and improve anemia . A meta‐analysis including 31 studies and 1580 patients on maintenance HD showed that treatment with ultrapure dialysate significantly suppressed OS and inflammation, as assessed by plasma levels of MPO, ox‐LDL, C‐reactive protein (CRP), and interleukin‐6 (IL‐6) .…”
Section: Hemodialysis Procedures and Osmentioning
confidence: 99%
“…39,40 Several investigators suggested that HD with ultrapure dialysate may decrease plasma concentrations of inflammatory and OS markers and improve anemia. [41][42][43][44][45][46][47] A meta-analysis including 31 studies and 1580 patients on maintenance HD showed that treatment with ultrapure dialysate significantly suppressed OS and inflammation, as assessed by plasma levels of MPO, ox-LDL, C-reactive protein (CRP), and interleukin-6 (IL-6) . 46 An ultrapure dialysate-based dialysis is relatively easy and inexpensive to achieve by using special dialysate filters.…”
Section: Ultrapure Dialysatementioning
confidence: 99%